Membangun Resiliensi dengan Konseling Kelompok: A Systematic Literatur Riview (SLR) - Hartini, Ayunda Apriliana; Istiqomah, Azizah Nur; Ulayya, Devina Lu’lu’; Islam, Diani Izzatul; Makhmudah, Ulya (Lembaga Yasin AlSys, 2025)
Resilience is the ability of individuals to overcome challenges that occur in their lives. Individuals who participated in group counseling tended to experience improved resilience. So that they can develop their resilience when facing a problem. Group counseling also helps students in understanding themselves and the problems they are facing. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with specific relevant topic areas and research questions. The number of articles found was 22 articles with characteristics that were in accordance with the research target. The results showed that resilience with group counseling could increase due to emotional support, instrumental support, information support, and reward support. Resilience building is focused on the core stage of group counseling when conveying the problem, this awareness is the first step in the formation of counseling resilience in group counseling. Increased resilience in group counseling can not only be applied in schools, but can also be applied in the general environment, which distinguishes only the implementation environment and counseling techniques used.